High incidence of cardiac dysfunction and response to antiviral treatment in patients with chronic hepatitis C virus infection - Poller, Wolfgang; Kaya, Ziya (Clinical research in cardiology, 2017)
AimsHepatitis C virus (HCV) has been associated with cardiomyopathies. Former anti-HCV therapies employing interferon could have serious side effects in patients with advanced heart failure since interferon may adversely impact upon cardiac function. We, therefore, examined whether the novel, interferon-free and highly virus-selective anti-HCV combination therapy might be applicable even in advanced or end-stage heart failure.Methods and resultsIn a retrospective series of HCV-positive patients admitted to our institution with suspected cardiac disease, coronary, valvular or hypertensive heart disease was diagnosed in 70/146 (47.9%). Among the others, 36/76 (47.4%) had myocardial disease: LV (32.9%)/RV (13.2%) hypertrophy, RV dysfunction (13.2%)/dilation (6.6%), severe diastolic dysfunction (7.9%), pulmonary hypertension (22.4%). One critically ill patient listed for heart transplantation (HTX) had previously not tolerated an interferon-based protocol. To still improve her chance of enduring transplant survival, we attempted an interferon-free virus-selective antiviral combination drug protocol under careful monitoring of possible side effects. Regarding clinical status she tolerated this treatment well, with the exception of transient severe hyponatremia requiring substitution. Her NYHA functional class improved from II-IV before to class II immediately after successful complete HCV elimination.ConclusionsWhereas prevalence of cardiac dysfunction and potential benefit from antiviral treatment was reported previously, there is lack of data regarding the response of patients with advanced heart failure. Since the highly HCV-selective drugs used above do not eliminate other cardiotropic viruses and have no direct effect on inflammation, massive improvement in such critically ill patients indicates a causal role of HCV in their cardiac failure, and of HCV elimination in their functional recovery.